Efficacy of Rainfall-Runoff Models in Loose Coupling Spacial Decision Support Systems Modelbase - Neto S.L.R.* (2019)
© 2019, Springer Nature B.V.The need for a prognosis for water resources management in Brazil means that studies with hydrological models are required, as part of a Spatial Decision Support System (SDSS). Choosing the model in a modelbase requires knowledge of the performance of the existing models in the specific situations in which they are to be applied. This paper evaluated the performance of two physically-based models and two numerical-based models in their ability to represent the rainfall-runoff process. The study occurred in a watershed in southern Brazil. Historical data series from the same periods were taken to calibrate and train the models, using two different periods to validate their efficacy. The results show that the SWAT and TOPMODEL models presented an inferior performance compared to the numerical-based models (RT and ANN). However, all the models presented satisfactory levels of efficacy and the potential for use in different management situations.